Pandangan Mahasiswa Mahasiswi IAIN Terhadap Negara Hukum Dan Penegakan Hukum Di Indonesia - Arya Eka Saputra; Yusuf Yusuf; Muhammad Romdony; Azizatun Hafizah (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
Since its independence, Indonesia has declared itself a state governed by law, as stated in the Preamble of the 1945 Constitution of the Republic of Indonesia. This noble ideal asserts that Indonesia is a state based on the rule of law, not merely power. However, the journey to realizing this ideal is fraught with challenges. Law enforcement in Indonesia faces serious issues such as weak rule of law, lack of accountability among law enforcers, low legal awareness among the public, and an inefficient judicial system. These problems lead to negative public perceptions of law enforcement in Indonesia. The public often sees law enforcement as unjust, with laws frequently "weak on the powerful and harsh on the powerless," where those in power often escape legal consequences while the underprivileged are easily punished. Additionally, the professionalism and integrity of law enforcement officials are often questioned, further tarnishing the image of law enforcement. This negative perception has severe implications for the stability and security of the nation, fostering public distrust that can lead to criminal and anarchic actions. addressing these issues requires continuous and comprehensive efforts involving all elements of the nation. The government needs to enhance transparency and accountability in law enforcement processes and enforce laws fairly and indiscriminately. The public also needs to actively supervise and criticize the performance of law enforcers. Surveys indicate that the majority of Indonesians have high hopes for the enforcement of laws in Indonesia, despite existing doubts and dissatisfaction with the slow and convoluted judicial process and the professionalism of law enforcers. The majority of respondents also acknowledge that corruption remains a serious issue requiring primary attention.